2021
DOI: 10.1007/s11307-021-01650-9
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Impact of [68 Ga]Ga-PSMA-11 PET/CT in Primary N and M Staging of Prostate Cancer Prior to Curative-Intent Surgery: a Prospective Clinical Trial in Comparison with mpMRI

Abstract: Purpose The main objective of this prospective study was to assess the value of gallium-68 prostate-specific membrane antigen ([68 Ga]Ga-PSMA-11) positron emission tomography/computed tomography (PET/CT) in primary N and M staging of intermediate- and high-risk prostate cancer (PCa) patients before planned curative-intent radical prostatectomy (RPE) and extended pelvic lymph node dissection (ePLND). The second objective was to compare the [68 Ga]Ga-PSMA-11 PET/CT findings with standard of care pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 30 publications
2
27
1
Order By: Relevance
“…A growing number of studies have found 68 Ga-PET/CT to offer significant value when diagnosing LNM. [25][26][27][28] As one of the primary Increases in PLR and NLR, as well as decreases in LMR, have been related to poorer overall survival outcomes in many cancers including PCa, 36,37 contradicting our results by a certain extent. We speculate that these differences may be associated with the stimulation of lymphocyte release from lymph nodes into the peripheral blood following tumor cell metastasis to these nodes.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…A growing number of studies have found 68 Ga-PET/CT to offer significant value when diagnosing LNM. [25][26][27][28] As one of the primary Increases in PLR and NLR, as well as decreases in LMR, have been related to poorer overall survival outcomes in many cancers including PCa, 36,37 contradicting our results by a certain extent. We speculate that these differences may be associated with the stimulation of lymphocyte release from lymph nodes into the peripheral blood following tumor cell metastasis to these nodes.…”
Section: Discussioncontrasting
confidence: 82%
“…A growing number of studies have found 68 Ga‐PET/CT to offer significant value when diagnosing LNM 25–28 . As one of the primary imaging parameters associated with PET/CT, SUVmax values offer valuable insight regarding tumor metabolic activity levels 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Few studies to date have explored the use of 68 Ga‐PSMA PET/CT model when diagnosing csPCa in patients with PI‐RADS 3 lesions 24,25 . In the present study, we found that men with PI‐RADS 3 with csPCa had a higher SUVmax and SUVT/BGp than men without csPCa, and which were independent risk factors for predicting csPCa.…”
Section: Discussionsupporting
confidence: 52%
“…In this study, the specificity of mpMRI was 0.77, which was lower than the above-mentioned results; however, this might be related to the small number of patients included in this study and the inclusion of patients with early-stage tumors. Prostatespecific membrane antigen positron emission tomography has also begun to be used in clinical practice, but it is more suitable for the diagnosis of lymph nodes and distant metastases of PCa, and its diagnostic performance is not better than that of mpMRI for primary tumors (17).…”
Section: Discussionmentioning
confidence: 99%